Heuristic Evaluation of UI/UX to Enhance Experience and Sales in E-commerce - Rendi Andika; Dram Renaldi (Komunitas Dosen Indonesia, 2024)
User experience and interface (UI/UX) are critical elements in e-commerce websites, where an unattractive design and lack of user engagement can negatively impact potential sales. This study was conducted to evaluate the effectiveness of the UI/UX on a company's e-commerce website, which has received complaints from users regarding the interface design and low purchase interest. The evaluation was conducted using the Heuristic Evaluation method, applying Nielsen's 10 principles with three evaluators to identify interface issues affecting user experience. The results of the study revealed significant weaknesses in three main principles: